2022
DOI: 10.1155/2022/7973504
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing the Cultivation Path of College Students’ Innovation and Entrepreneurship Ability from the Perspective of the Internet

Abstract: At present, the path of college students’ innovation and entrepreneurship training is still not perfect, especially the understanding and mathematics of college students’ innovation and entrepreneurship concepts. Therefore, it is urgent to guide college students to adhere to the ideal of innovation and entrepreneurship, cultivate the spirit of innovation and entrepreneurship, cultivate the morality of innovation and entrepreneurship, and improve the comprehensive ability of innovation and entrepreneurship of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Reviewing relevant research, it can be found that the understanding of the connotation of business model innovation is mostly carried out from different perspectives such as profitability, value chain, and activity system. The literature shows that the level of business activity mainly depends on the external environment and the group ecology theory discusses the impact of the external environment on the survival and development of startups from a macro level [10]. Different market capacities, regional differences, institutional norms, and political environments can all have an impact on the survival of enterprises.…”
Section: Related Workmentioning
confidence: 99%
“…Reviewing relevant research, it can be found that the understanding of the connotation of business model innovation is mostly carried out from different perspectives such as profitability, value chain, and activity system. The literature shows that the level of business activity mainly depends on the external environment and the group ecology theory discusses the impact of the external environment on the survival and development of startups from a macro level [10]. Different market capacities, regional differences, institutional norms, and political environments can all have an impact on the survival of enterprises.…”
Section: Related Workmentioning
confidence: 99%
“…College students have relatively rich knowledge reserves and also creativity which is lacked by other high-level intellectuals, but they also need to be psychologically ready for the great risks and challenges of entrepreneurship. Having entrepreneurial resilience will help college students actively cope with the inevitable setbacks and pressures they will face in the entrepreneurial process [8][9][10][11][12][13][14][15]. Due to the constraints of the entrepreneurial ecological environment and the heterogeneity of the individual college students and their interpersonal relationships and situations, some specific problems like psychological potential development and stress buffering effect in the process of college students' entrepreneurial resilience cultivation have not been fundamentally resolved [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, some report shows that only less than 3% of college graduates will choose to start businesses after graduation. To improve this situation, it is necessary to change college student's entrepreneurial intention through entrepreneurship education to allow them to better understand how capable they are of controlling the process of entrepreneurial activities and encourage their entrepreneurial behaviors [10][11][12][13][14][15][16][17][18][19][20][21]. Therefore, exploring the influence mechanism of entrepreneurship education on college students' entrepreneurial intention has certain practical significance, and will provide some reference for the innovations in college students' entrepreneurial ability training mode and the formulation of relevant supporting policies.…”
Section: Introductionmentioning
confidence: 99%